Working Memory Capacity of Biological Motion’s Basic Unit: Decomposing Biological Motion From the Perspective of Systematic Anatomy - Wang, Chaoxian; Zhou, Yue; Li, Congchong; Tian, Wenqing; He, Yang; Fang, Peng; Li, Yijun; Yuan, Huiling; Li, Xiuxiu; Li, Bin; Luo, Xuelin; Zhang, Yun; et al. (Frontiers in Psychology, 2022)
Many studies have shown that about three biological motions (BMs) can be maintained in working memory. However, no study has yet analyzed the limitations of experiment materials used, which partially affect the ecological validity of the experiment results. We use the perspective of system anatomy to decompose BM, and thoroughly explore the influencing factors of working memory capacity (WMC) of BMs, including presentation duration, joints to execute motions, limbs to execute motions, type of articulation interference tasks, and number of joints and planes involved in the BM. We apply the change detection paradigm supplemented by the articulation interference task to measure the BM WMC of participants. Findings show the following: the shorter the presentation duration, the less participants remembered; the more their wrist moved, the less accurate their memory was; repeating verbs provided better results than did repeating numerals to suppress verbal encoding; the more complex the BM, the less participants remembered; and whether the action was executed by the handed limbs did not affect the WMC. These results indicate that there are many factors that can be used to adjust BM memory load. These factors can help sports psychology professionals to better evaluate the difficulty of BMs, and can also partially explain the differences in estimations BM WMC in previous studies.